Zonal selectivity by sensitivity modulation in linear tetrapolar impedance sensors - Moretti, Fabián N. (2018)
This work investigates the behaviour of a tetrapolar impedance sensor due to sensitivity issues caused by inherent method measurement when inter-electrode spacing is changed. Finite Element Method (FEM) modelling of the sensitivity spectra was computed to analyse maximum sensitivity levels in desired zones of the sample and non-common known and unintuitive phenomenon as negative sensitivity lobes inside the sensitivity distribution field. Sensitivity maps as a function of electrode position were obtained and maximum sensitivity curves were extracted to identify the best configuration for major sensitivity contribution to characterize a specific sample section. A prototype of a linear tetrapolar sensor array of planar microelectrodes for sensing ionic samples was used for the computational modelling and a brief experimental validation was performed to show the vertical stratification process. The analysis shows that it is possible to have zonal selectivity in the impedance measurement and characterize a desired zone of the sample modulating the sensitivity, changing the electrode position by a scale pattern. This manuscript offers a novel approach for designing tetrapolar sensors based on analyzing maximum sensitivity curves obtained by FEM modelling.